Oligomerization of Dicyclopentadiene Fraction with the Use of Monoalkohyterchloride Titanium as a Catalyst; Химия и химическая технология в XXI веке; Т. 2 - Volchok E. V. (Секция 7. Химия и химическая технология, 2011)
Заглавие с титульного листа